Impact of Job Stress, Psychological Well-Being, and Employee Training on Job Performance - Thida Cho Lwin; Harif Amali Rivai; Rivai, Harif Amali (AMAR (Andalas Management Review), 2025)
Background – Europe & Asia Beverages Co., Ltd. is a top beverage manufacturer in Myanmar, offering soft drinks, energy drinks, and bottled water. As the industry grows, employees face rising job stress due to production demands and quality control measures. Psychological well-being and training are crucial for improving performance, yet often overlooked. This study examines how these factors impact employee outcomes at Europe & Asia Beverages Co., Ltd. Aim – This study aims to examine the effects of job stress, psychological well-being, and employee training on job performance in Myanmar’s beverage industry, with a specific focus on Europe & Asia Beverages Co., Ltd. Design / methodology / approach – This study employs a quantitative research approach to examine the impact of job stress, psychological well-being, and employee training on job performance at Europe & Asia Beverages Co., Ltd. in Myanmar. Data were collected using structured questionnaires distributed to 150 employees, including managers, supervisors, and laborers. The study utilized a cross-sectional design and analyzed the data using descriptive statistics, reliability tests, and SmartPLS software to test hypotheses and assess relationships between variables. Findings – The findings reveal that psychological well-being and employee training significantly and positively influence job performance. Employees with higher psychological well-being exhibit better focus, motivation, and job satisfaction, leading to improved performance. Research Implication – This research highlights the importance of fostering psychological well-being and investing in employee training to enhance job performance. Organizations should prioritize mental health initiatives, such as counselling and mindfulness programs, and implement structured training programs tailored to employees' needs. Limitations – The study's reliance on self-reported data introduces potential biases, such as social desirability bias. The cross-sectional design limits the ability to establish causal relationships between variables. Furthermore, the sample is restricted to a single organization in Myanmar's beverage industry, which may limit the generalizability of the findings to other industries or cultural contexts.